Thermal and Optical Radiation Effects on Liposomes Encapsulated Haemoglobin - A. Alfahhad, Marwan (Asian Journal of Chemistry, 2010)
Synthetic red blood cells known as liposomes encapsulated haemoglobin (LEH) is a material that offers an excellent alternative to substitution blood since the chemical composition of the liposomes encapsulated oxyhaemoglobin (Oxy LEH), is similar to that of the natural blood cells. Unfortunately, this alternative, like the natural blood, has a limited shelf life at room temperature due to thermal, and/or solar (optical) radiations exposure. In this study experiments were run on LEH assays, with and without protection additives. to weigh up the effect of exposing LEH to thermal effect. using a digital controlled oven, and to optical radiations. using an appropriate apparatus to stimulate the solar optical radiations. Constant evaluation of the acceptability of this artificial blood alternative was done with the help of an advanced computerized technique. The results of the experiment have shown that exposing LEH to thermal and optical radiations leads to a reduction of the concentration of the oxyhaemoglobin and a' heightened of the concentration of the methaemoglobin. The rate of LEH degradation in the two treatments was linked to the time in which they were exposed both to the thermal and optical radiations effects. Antioxidants. ascorbic acid and α-tocopherol were used in order to conserve and guard the prepared LEH from the degradation that happens to it due to the effects of both thermal and optical radiations.